Sweet potato flour and starch extraction and their utilization in drop cookies - Pongco, Jan Raymond L. (2003)
ABSTRACT Fresh sweet potatoes (Ipomea batatas Lam,), of the Super Bureau (VSP-6) variety, were processed into sweet potato flour (SPF) and sweet potato starch (SPS) utilizing mechanical processing and wet extraction method, respectively. The moisture content, physico-chemical, parameters, color and the filth content of the flour and starch were determined using standard methods. The resulting starch and flour were further tested for their feasibility in the manufacture of drop cookies. Different combinations of composite flour were used to evaluate which level of substitution of all-purpose flour (APF) by sweet potato flour (SPF) or sweet potato starch (SPS) could be most desirable to the consumers. Treatments containing 100% APF (T1), 75% APF and 25% SPF (T2), 75% APF and 25% SPS (T3), 50% APF and 50% SPF (T4), 50% APF and 50% SPS (T5), 25% APF and 75% SPF (T6), 25% APF and 75% SPF (T7), 100% SPF (T8), 100% SPS (T9) were evaluated for cookie height, spread ratio, color evaluation and sensory testing through Quantitative Descriptive Analysis (QDA). Shelf life analyses, such as free fatty acid determination, microbial analysis specific for molds and yeasts, and sensory evaluation of the most desirable formulation (50% APF and 50% SPF) were also done. Final moisture content of both SPF and SPS were 14%, with the pH of SPF (5.8) being lower than that of SPS (6.4). In terms of the gelatinization temperature, SPF established a relatively much higher value as compared to SPS. Rapid Visco Analyzer disclosed SPS as having lower pating attributes correlating it to poor eating quality. Furthermore, SPF exhibited higher resistance to breakdown and higher tendency towards retrogradation as compared to SPS. Color evaluation revealed that SPF has distinctive darker color than SPS. Drop sweet potato cookies evaluation indicated significant differences in spread ratio and the cookie height among nine treatments. Color evaluation showed that SPF-substituted cookies were darker in color than SPS-substituted ones. Significant differences (p<0.05) were also observed via analysis of variance among treatments in terms of color, thickness, grittiness, springy character and sweetness. Treatments that utilized sweet potato flour in any proportion established higher intensity of color as compared to those which used sweet potato starch and all-purpose flour. Treatments which employed high percentages of sweet potato starch exhibited low values in the thickness attribute. The grittiness of the drop cookies increased as the level of substitution by sweet potato flour and sweet potato starch increased except treatments 8 (100% SPF) and 9 (100% SPS). An inverse trend was shown in the springy trait of the cookies as the amount of substitution was increased. Similarly, a decrease in the sweetness of the samples was observed as the level of substitution was increased; the SPS substituted treatments had lower sweetness values relative to the SPF substituted ones. Though of low values, free fatty acid (FFA) was observed to have increased during the shelf life analysis of the preferred drop cookie formula (50%SPF, 50%APF). Moreover, the microbial load was minimal during the storage study and sensory evaluation showed that buttery flavor, dry texture, grittiness, oiliness, rancidity, springy character, sweet taste, camote-like aroma, thickness and general acceptability of the sweet potato cookies all manifested significant differences (p<0.05). As the storage time increased, a decrease in thickness, camote-like aroma, oiliness, springy trait and grittiness values were observed. Dryness and the sweetness of the samples increased during storage. Consistent with the percent free fatty acid values obtained, the rancid taste of the stored cookie developed. Finally, the buttery after-taste and the general acceptability of the drop cookies declined in the middle of the storage period and evidently increased in the latter part.